La Franc-maçonnerie, entre cité céleste et cité terrestre : divisions et équilibrages internes au sujet du théisme, de la religion et des questions sociétales - Céline Bryon-Portet (Amnis)
This text studies the paradoxical position of Freemasonry, which tries to conciliate spiritual quest and socio-political engagement. First, the author shows that Freemasonry contains some religious aspects because it cultivates the sacred through an initiation and ritual practices, even if it can’t be considered as a religion: in fact, it is non-dogmatic, and many obediences refuse to evocate God during their ceremonies and the question of belief in a Superior Being is source of disputes between the lodges. After that, the author points the fact that freemasons who belong to the liberal branch of Freemasonry want to participate to the evolution of the laws in profane society and to defend the principles of secularism, according to the Masonic objective, consisting in making progress the Humanity. This median way, consisting in refusing the dualistic approaches by building both a celestial city and a terrestrial city, constitutes an original philosophy, which is able to suit to some contemporary people who don’t want to separate idealism and materialism.